The effect of financial literacy on saving : a study on Malaysian population / Saleh Tabiani - Tabiani, Saleh (2010)
Personal saving is valuable for the whole nation. Saving of today, affects the consumption of future, because the saved money is invested in financial assets and goes through investments in industries, factories, prosperities, and other kinds of investment that is necessary for country’s growth. Saving also can help the country recover from financial crisis more easily. In this study the factors that are likely to increase personal saving are measured. These factors include the financial literacy of individuals, saving motivation, and socio-demographic characteristics such as, age, gender, ethnicity, number of children, nationality, income, and education level. The main focus of this study is to examine the effect of financial literacy on saving amongst individuals, which is found to be very important. Results also show that different saving motivations increase saving. Moreover age, gender and number of children were found significant factors which can improve saving.